Penatalaksanaan Fisioterapi Pada Kasus Carpal Tunnel Syndrome Bilateral Dengan Modalitas Ultrasound Dan Nerve Gliding Exercise Di Rsud Cililin Kabupaten Bandung Barat - Ika Rahman; Putri Apriliana Riskianti; Abdul Qudus (Dinasti Health and Pharmacy Science, 2026)
Bilateral Carpal Tunnel Syndrome is a condition caused by compression of the median nerve within the carpal tunnel, resulting in pain, tingling, muscle weakness, and limitations in hand function that may interfere with daily activities. This study aimed to determine the effectiveness of physiotherapy interventions using ultrasound and nerve gliding exercise in reducing pain, improving range of motion (ROM), and enhancing hand functional ability. This study used a descriptive method with a case study approach involving one patient with bilateral Carpal Tunnel Syndrome at RSUD Cililin. Evaluation was performed using the Visual Analog Scale (VAS), goniometer, and Wrist Hand Disability Index (WHDI). After six therapy sessions, pain decreased in both hands, wrist flexion improved from 45° to 50°, and WHDI scores decreased from 32% to 24% in the right hand and from 32% to 28% in the left hand. These findings indicate that the combination of ultrasound and nerve gliding exercise may help reduce pain, improve ROM, and enhance hand functional ability in bilateral Carpal Tunnel Syndrome cases.